Improving first-line therapy of advanced ovarian cancer – the AGO Ovarian Cancer Study Group perspective. (1st October 2003) - Du Bois, A.; Pfisterer, J.; Meier, W.; Wagner, U.
Abstract : This review displays the AGO Ovarian Cancer Study Group approach towards evaluation of improvement options in first-line therapy of advanced ovarian cancer. Prospectively randomized phase III trials evaluating the addition of newer drugs to standards carboplatin-paclitaxol (TC) as well as pilot trials evaluating new treatment modalities like anti-idiotype CA 125 antibodies or epidermal growth factor receptor (EGFR) modulation are presented.